2017
DOI: 10.1519/jpt.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Function After a 6-Month Walking Intervention in Patients With Intermittent Claudication Who Are Obese or Nonobese

Abstract: Background and Purpose Both obesity and peripheral artery disease (PAD) limit function and may work additively to reduce mobility. The purpose of this study was to compare the effects of a 6-month, center-based walking program on mobility function between adults who are weight-stable obese and non-obese with PAD. Methods This is a secondary data analysis of two combined studies taken from previous work. Fifty-three adults with PAD and intermittent claudication participated in 6-months of treadmill training o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 44 publications
1
5
0
Order By: Relevance
“…In fact, compared to T2 data, the perceived pain at T3 was 81.7% lower as a result of walking with FES (Table 1). Direct comparison of the crossover data to published studies' effects on IC pain reduction is not possible because of experimental differences in measuring pain intensity [18,21]. However indirect, approximate comparison of success in pain reduction after endovascular intervention reported by Land et al [22] appears at least comparable to the pain reduction after walking with FES for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, compared to T2 data, the perceived pain at T3 was 81.7% lower as a result of walking with FES (Table 1). Direct comparison of the crossover data to published studies' effects on IC pain reduction is not possible because of experimental differences in measuring pain intensity [18,21]. However indirect, approximate comparison of success in pain reduction after endovascular intervention reported by Land et al [22] appears at least comparable to the pain reduction after walking with FES for 8 weeks.…”
Section: Discussionmentioning
confidence: 99%
“…The crossover data (T3) documented outcome measures for the nine patients enrolled in the crossover phase. Five measures included: 1) Walking distance was determined by measuring meters traveled during the 6MW test [18]. If patients were unable to walk the full six minutes, they were allowed to sit and rest until they were ready to continue.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…The increased leg pain with activity may deter those with PAD from participating in exercise as a means of weight loss. In a 6-month study of older adults with PAD we previously found that individuals with obesity who did not participate in an exercise intervention were susceptible to greater declines in mobility when compared with normal-weight peers (Addison et al, 2017). Others have reported similar findings and individuals with the combination of obesity and PAD claudicate more quickly with activity (Dias et al, 2009), and experience greater declines in calf-muscle area (Raval et al, 2012) and gait speed (McDermott et al, 2006) when compared with normal-weight individuals with PAD.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity is a known risk factor for PAD and up to 60% of individuals with PAD are overweight or obese (McDermott et al, 2001). Obesity is one of the leading causes of disability in older adults without PAD, and among those with PAD obesity results in a further functional burden (Addison et al, 2017; Dias et al, 2009; McDermott et al, 2006; Raval et al, 2012). Older adults with PAD and obesity experience claudication pain more quickly (Addison et al, 2017; Dias et al, 2009), require longer to recover after exercise (Addison et al, 2017; Dias et al, 2009), and experience greater declines in physical function when compared with normal-weight individuals (Addison et al, 2017; Dias et al, 2009; McDermott et al, 2006; Raval et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation